ADDITION OF PETEK FISH (LEIOGNATHUS SP.) PROTEIN HYDROLYSATE TO DRY NOODLES - Ramli, Ramli; Jasila, Ismi (Agripreneur : Jurnal Pertanian Agribisnis, 2025)
Petek fish has a very high protein content, reaching 32 grams from 100 grams of fish weight. Making fish protein hydrolysate from petek fish can help add protein to food products. Food products that can be added with functional protein to increase and improve their protein content are dry noodles. The purpose of this study was to determine the effect of different concentrations of fish protein hydrolysate from petek fish on the protein content and organoleptic characteristics of dry noodles. The method used in the study was a Completely Randomized Design (CRD) with the addition of petek (Leiognathus sp.) fish protein hydrolysate to dry noodles consisting of several different concentrations, namely A1 (0%), A2 (2%), A3 (4%), and A4 (6%). The parameters to be observed in this study were protein content and organoleptic characteristics in each treatment. The results showed that Analysis of the protein content and organoleptic properties of dried noodles with the addition of fish protein hydrolysate showed significant differences between the different treatments. Treatment A1 was the best overall, while treatment A4 could be considered an alternative if increasing protein is a priority.